Fostering East Java Msme Sustainability Through Green Accounting And Environmental Management Accounting - Anisaul Hasanah; Parasdya Pandhu Andanawarih; Dini Ayu Pramitasari (Universitas Muhammadiyah Tangerang, 2026)
This study examines the effects of green accounting awareness (GAA) and environmental compliance (EC) on MSME sustainability, with environmental management accounting (EMA) as a mediating variable. Using a quantitative cross-sectional survey, primary data were collected through structured questionnaires from MSME owners and managers in East Java, Indonesia, selected purposively based on their direct involvement in financial or environmental decision-making. Of 300 questionnaires distributed, 262 were complete and usable. The hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 3. The results show that GAA has no significant direct effect on MSME sustainability, suggesting that environmental knowledge alone is insufficient without effective managerial implementation. In contrast, EC has a significant positive effect on sustainability. GAA and EC both positively influence EMA, and EMA significantly contributes to MSME sustainability. Moreover, EMA mediates the relationships between GAA and sustainability, as well as between EC and sustainability, indicating that environmental knowledge and regulatory compliance are more effective when embedded in systematic accounting practices. These findings highlight EMA as a strategic capability that converts environmental awareness and compliance into sustainable performance. Policymakers and MSME support institutions should strengthen EMA-based capacity building, environmental cost management training, and standardized reporting practices to improve compliance, decision-making, and long-term sustainability.